Enhancing Writing Quality and Higher-Order Thinking Skills among EFL Learners through Collaborative Writing - Jitlada Moonma (JET (Journal of English Teaching), 2026)
This study investigated the extent to which collaborative writing activities enhanced writing quality and higher-order thinking skills among Thai EFL learners. Employing a quasi-experimental mixed-methods design, the study involved 65 second-year English majors enrolled in a writing course at a public university in northern Thailand during the 2025 academic year. Participants were purposively selected and completed writing tasks under three instructional conditions: group, pair, and individual writing. Quantitative data were obtained from writing assessments and self-assessment questionnaires, while qualitative data were collected through semi-structured interviews. Repeated-measures ANOVA revealed a significant effect of instructional condition on writing quality, F(2,128) = 24.67, p < .001, η² = .28. Group writing produced the highest scores (M = 11.39), followed by pair writing (M = 10.31) and individual writing (M = 9.16). Group-based collaboration also promoted higher levels of analyzing, evaluating, and creating. Interview findings indicated that collaborative interaction fostered idea generation, peer scaffolding, reflective thinking, and confidence development. These findings underscore the pedagogical value of collaborative writing for enhancing cognitive engagement and writing performance in EFL classrooms.